POSITION OF CIRCULAR LETTER OF THE SUPREME COURT AS A FOLLOW-UP FROM THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 37/PUU-IX/2011 - Suparto; Zulkifli (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
Judicial review of Law Number 13 of 2003 concerning Manpower is carried out to the Constitutional Court (MK), one of the reasons is the implementation of Article 155 paragraph (2) has the potential to create legal uncertainty, because there are multiple interpretations related to the term